Safety and clinical efficacy of immune checkpoint inhibitors in pediatric hepatocellular carcinoma: a case report and review of the literature - Zhong, Xiaoting; Wen, Xuejiao; Wang, Xinping; Ye, Jianming; Huang, Li; Wang, Jing; Chi, Jun; Zeng, Xiaoli (Frontiers in Oncology, 2025)
BackgroundPediatric hepatocellular carcinoma (HCC) is rare, with surgical resection and liver transplantation as primary treatments. No standard options exist for unresectable/metastatic disease. Although immune checkpoint inhibitors (ICIs) show efficacy in adults, their pediatric safety and efficacy remain unestablished.Case presentationWe report two cases of pathologically confirmed pediatric HCC treated with ICIs. The first patient underwent transhepatic arterial chemoembolization (TACE) and sintilimab immunotherapy. The second patient received oral sorafenib-targeted therapy followed by sequential immunotherapy with tirilizumab and sintilimab. The only adverse reaction of grade 3 or higher was skin rashes.MethodsWe summarized the characteristics and treatment strategies of two pediatric HCC cases (<18 years of age) treated with ICIs at our center. We reviewed previous case reports, case series, and clinical studies on ICI treatment for pediatric HCC. All cases were evaluated for efficacy using the HCC-modified Response Evaluation Criteria in Solid Tumors every 2–3 cycles after the treatment and serial tracking of alpha-fetoprotein (AFP) levels. Treatment-related adverse reactions were graded according to the Common Terminology Criteria for Adverse Events version 5.0.ResultsThe first patient underwent two cycles of targeted therapy and immunotherapy, after which the tumor was assessed as having progressed. The patient then received TACE treatment and three consecutive cycles of sintilimab and lenvatinib combination therapy, resulting in stable tumor evaluation. However, after discontinuing lenvatinib, the patient’s AFP levels rose sharply, and one cycle of HAIC therapy was administered, successfully lowering the AFP levels. The second patient did not respond to immunotherapy despite the combination of targeted therapies. One patient treated with sintilimab developed a grade 3 rash, although it did not occur upon re-administration of the drug. No severe adverse reactions were observed in patients treated with tirilizumab. In the literature, most pediatric HCC cases were fibrolamellar carcinomas, which showed encouraging results after treatment with pembrolizumab, leading to longer patient survival.ConclusionThe efficacy and safety of ICIs in pediatric HCC require further validation. Ongoing prospective studies will determine their clinical role, necessitating cautious application until robust evidence emerges.